Avaliação da vitalidade de cordeiros nascidos de partos eutócicos e cesarianas - Bovino, Fernanda [UNESP]; Camargo, Diogo Gaubeur de [UNESP]; Araújo, Marcelo Augusto de [UNESP]; Costa, Felipe de Paiva [UNESP]; Santos, Paulo Sergio Patto dos [UNESP]; Mendes, Luiz Claudio Nogueira [UNESP]; Peiró, Juliana Regina [UNESP]; Feitosa, Francisco Leydson Formiga [UNESP] (Revista Pesquisa Veterinaria Brasileira, 2014)
The aim of this study was to evaluate vitality of lambs born by normal delivery and cesarean section, during 48 hours of life, by means of APGAR score, behavior and vital parameters. The first group was formed with lambs born by normal delivery (NORMAL) and the other two groups were formed with lambs born by cesarean sections, but with two different anesthetic protocols, one used inhalation anesthesia (INAL) and the other total intravenous anesthesia (TIVA). Lambs in the NORMAL group obtained higher pontuation in Apgar score. At birth and 15 minutes, 93.75% of lambs NORMAL group obtained maximum score (7-8), while no lambs born by cesarean section obtained this score at birth. At 15 minutes, 25.00% of the lambs INAL group received the same score. The heart rate remained virtually unchanged for both groups, with a tendency to decrease values, at 24 hours for group TIVA animals. The respiratory rate at birth for the animals delivered by cesarean section (26 +/- 25 bpm, INAL; 5 +/- 5 bpm, TIVA) was significantly lower than for the ones of the normal delivery. Nevertheless, that value at 60 minutes was found quite close. A tendency for decreasing temperature values was verified until the 15 minutes in all groups, lasting until 60 minutes in animals in the TIVA group. Lambs born by c-section have lower vitality than lambs born by normal delivery.

O trabalho teve como objetivo avaliar a vitalidade de cordeiros nascidos de parto normal e de cesariana, ao longo das primeiras 48 horas de vida, por meio da pontuação no escore Apgar, do seu comportamento e da aferição dos parâmetros vitais. Os animais foram divididos em três grupos, sendo o primeiro constituído por cordeiros nascidos de parto normal (NORMAL) e os outros dois de cesarianas, porém com dois protocolos anestésicos diferentes, ou seja, por meio de anestesias inalatória (INAL) e total intravenosa (ATI). Os animais do grupo NORMAL obtiveram pontuação maior no escore Apgar. Ao nascimento e aos 15 minutos, 93,75% dos cordeiros do grupo NORMAL obtiveram pontuação máxima (7-8), enquanto que nenhum dos animais nascidos de cesarianas atingiu essa pontuação, ao nascimento. Aos 15 minutos, 25,00% dos animais do grupo INAL recebeu a mesma soma de pontos. A frequência cardíaca permaneceu praticamente inalterada para ambos os grupos, com tendência à diminuição dos valores, às 24 horas, para animais do grupo ATI. A frequência respiratória (FR) ao nascimento foi significativamente menor nos animais nascidos de cesarianas (26±25mpm, INAL; 5±5mpm, ATI), encontrando-se, porém, próxima aos valores dos animais do grupo NORMAL, aos 60 minutos. Constatou-se tendência à diminuição nos valores de temperatura até os 15 minutos de vida em todos os grupos, prolongando-se, até os 60 minutos, nos animais pertencentes ao grupo ATI. Os animais nascidos de cesarianas possuem vitalidade inferior aos nascidos de partos normais.
Evaluation of vitality in lambs born by normal delivery and cesarean section
Keywords: Sheep; Newborn; APGAR; Cesarean section; Vital parameters; Ovino; Neonato; Apgar; Parto eutócico; Cesariana; P, parâmetros vitais